Excavations at Baleshare (Scottish Historical and Archaeological Internet Reports, 2003)
Details of site location are followed by a brief description of the 48-metre length of midden deposit prior to this excavation, and an account of earlier work. The excavation is described in a series of 29 blocks. Remains include midden deposits, dumped deposits, a grave pit containing an inhumation, substantial structural phases, floor layers associated with a circular structure and cultivation layers. Artefacts and ecofacts comprise pottery (including a near complete vessel), a quernstone, slag and animal bone. Many radiocarbon dates are integrated into the archaeological description.